Rethinking the Role of the Renin-Angiotensin System in the Pandemic Era of SARS-CoV-2 - Fabio Angeli; Martina Zappa; Paolo Verdecchia (Journal of Cardiovascular Development and Disease, 2023)
After assessing the levels of spread and severity of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, academic literature focused on the pathophysiology of coronavirus disease 2019 (COVID-19) [...]